2021
DOI: 10.1002/est2.243
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium modified defatted spent coffee catalysts for supercapacitor and methanolysis application

Abstract: Currently, a novel green material, defatted spent coffee ground (DSCG), is employed as a support to prepare DSCG supported Ru (DSCG‐Ru) material. DSCG and DSCG‐Ru materials are characterized by advanced surface analytical techniques such as N2 adsorption‐desorption, X‐ray diffraction, X‐ray photoelectron spectroscopy, and H2‐temperature‐programmed reduction. Characterization results revealed that DSCG‐Ru was prepared successfully. First, DSCG‐Ru is prepared at varying Ru contents on deoiled coffee waste and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 55 publications
0
17
0
2
Order By: Relevance
“…Basically, the activated carbon preparation method, the type of biomass support material, the activating agent, the type of electrolyte used, the temperature at which the biomass is burned, and the additive are effective on the capacitance values of the electrodes to be produced. In the literature, many supercapacitors have been designed using many biomass such as corn stalk, 18 lotus stem, 25 pomegranate peel, 26 tea factory waste, 27 pine cone biomass, 28 palm kernel shells, 29 loofah sponge, 30 and defatted spent coffee 31 . Considering the results, it is thought that especially Qui‐pure and Qui‐KOH materials will gain popularity in electrical energy storage, thanks to their stable structures and high capacities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, the activated carbon preparation method, the type of biomass support material, the activating agent, the type of electrolyte used, the temperature at which the biomass is burned, and the additive are effective on the capacitance values of the electrodes to be produced. In the literature, many supercapacitors have been designed using many biomass such as corn stalk, 18 lotus stem, 25 pomegranate peel, 26 tea factory waste, 27 pine cone biomass, 28 palm kernel shells, 29 loofah sponge, 30 and defatted spent coffee 31 . Considering the results, it is thought that especially Qui‐pure and Qui‐KOH materials will gain popularity in electrical energy storage, thanks to their stable structures and high capacities.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, many supercapacitors have been designed using many biomass such as corn stalk, 18 lotus stem, 25 pomegranate peel, 26 tea factory waste, 27 pine cone biomass, 28 palm kernel shells, 29 loofah sponge, 30 and defatted spent coffee. 31 Considering the results, it is thought that especially Qui-pure and Qui-KOH materials will gain popularity in electrical energy storage, thanks to their stable structures and high capacities.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…As an example of some biomass supercapacitors in previous studies, while the capacitance of biopolymer electrodes prepared with corn starch containing lithium acetate and glycerol was calculated as 33 F/g by Shukur et al, 72 Teog et al 70 calculated the capacitance of polymer electrodes prepared with corn starch containing lithium perchlorate and barium as 16.22 F/g. In another study, Akdemir et al 74 prepared the ruthenium material supported by defatted spent coffee ground and examined both the catalytic activity of sodium boron hydride in the methanolysis reaction and calculated the capacitance of the electrodes as 43 F/g by measuring the supercapacitor of this material. Finally, Inal et al 39 investigated the catalytic activity of Microcystis aeruginosa microalgae supported manganese material in the methanolysis reaction of sodium boron hydride, and they calculated the capacitance of the electrodes as 40 F/g by measuring the supercapacitor of this material.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, together with catalyst studies, a super capacitor was developed to determine the energy storage capacity of the material used. By the way, this material was named as cap‐cat in the literature 38‐41 …”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have shown that carbon materials named as "cap-cat" (capacitor-catalyst) can be used multi-functionally as both catalyst material and supercapacitor material. 35,36 In this context, a supercapacitor cell was prepared by using PP-H 3 PO 4 -Pd catalyst as the electrode material by a twoelectrode system.…”
Section: Introductionmentioning
confidence: 99%